Evolvable Skin Electronics by In Situ and In Operando Adaptation (Adv. Funct. Mater. 4/2022). (19th January 2022) - Kim, Kyun Kyu; Choi, Joonhwa; Kim, Joon‐Hong; Nam, Sangwook; Ko, Seung Hwan
Abstract : Skin Electronics In article number 2106329, Seung Hwan Ko and co‐workers report a rewritable wearable electronics manufacturing platform that is capable of simultaneously evolving its structure by laser direct drawing and erasing. This device concurrently adapts to change in users and purpose of the device by making optimization, modification, and expansion, which is further applied to measuring human physiological signals and human motions.